(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article argues that Romanticism in England is characterized by its national distinctiveness. The works of English romantics reflect a national tradition of portraying life in fantastic-utopian, allegorical, and symbolic forms, as well as a tradition of dramatic treatment of lyrical themes. It is also noted that the influence of Enlightenment ideas remained strong in English Romanticism. Furthermore, the sublime was not always understood as something exceptional; rather, it was often revealed in what was simple, ordinary, and outwardly unremarkable.